Pelvic Hydatic Cyst Mimicking An Ovarian Neoplasm: A Case Report - Akpınar, Funda; Güvendağ Güven, Seda; Bedir, Recep (Gynecology Obstetrics & Reproductive Medicine, 2012)
Hydatid disease is a zoonotic infection that affects a large number of and animals especially in livestock producing countries like Turkey. A case of pelvic echinococcal cyst is presented, which gives the apperance of a malignant ovarian neoplasm. Patient’s past history of hepatic surgery gave a clue, that it could be echinococcosis, but since the reports were lost, we could not confirm our suspicion. Although their localization in the pelvis is rare, echinococcal cyst should be kept in mind in the differentia ldiagnosis of pelvic masses, especially in patients of endemic regions.